Nickel-doped lanthanum cerate nanomaterials as highly active electrocatalysts - Butt, Tehmeena Maryum; Erum, Safia; Mujtaba, Ayesha; Medvedev, Dmitry; Janjua, Naveed Kausar (Frontiers in Chemistry, 2022)
The efficient oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) catalyst materials are crucial in the energy research domain due to their tunability. Structural modification in perovskites such as lanthanum cerates (LaCeO3) upon doping at A or B sites significantly affects the surface activity and enhances the catalysis efficacy. Herein, B-site nickel-doped lanthanum cerate (LaCe1-xNixO3±δ) nanopowders were applied as ORR indicators in high-temperature electrochemical impedance spectroscopy for solid-oxide fuel cell (SOFC) tests and in cyclic voltammetric OER investigations in alkaline medium. The integration into SOFC applications, via solid-state EIS in a co-pressed three-layered cell with LCNiO as cathode, is investigated in an oxygen–methane environment and reveals augmented conductivity with temperatures of 700–850°C. The higher electrokinetic parameters—including diffusion coefficients, Do heterogeneous rate constant, ko, and peak current density for OER in KOH-methanol at a LCNiO-9-modified glassy carbon electrode—serve as robust gauges of catalytic performance. CV indicators and EIS conductivities of LaCe1-xNixO3±δ nanomaterials indicate promising potencies for electrocatalytic energy applications.